Pilot National Asian American Political Survey (PNAAPS), 2000-2001 - Lien, Pei-te ([Verlag nicht ermittelbar], 2004)
The purpose of this multicity, multiethnic, and multilingual survey was to provide a preliminary attempt to gauge the political attitudes and behavior of Asian Americans on a national scale. Major areas of investigation include ethnic identity, acculturation, homeland politics, voting and other types of political participation, political ideology, political partisanship, opinions on various social issues, social connectedness, racial integration, and group discrimination. Respondents were asked whether people of Asian descent had a great deal in common culturally, what they thought were the most important problems facing their own ethnic group, whether they belonged to any organization that represented the interest of their group, and their knowledge of the Wen Ho Lee case, the 8-20 Initiative, and other news stories and information about Asians in the United States. Political questions probed respondents' general interest in politics, whether and for whom they voted in the 2000 presidential election, their general knowledge of the presidential election process, the kinds of political activity in which they participated, their feelings about Asian-American candidates, their involvement with political parties, their level of trust in local, state, and federal government officials, self-identity with regard to a liberal vs. conservative stance on political matters, party affiliation, and how active they were in political parties or organizations in their home country if born outside of the United States. Respondents were also asked about their attitudes on such topics as immigration, affirmative action, job training, educational assistance, preferences in hiring and promotion, marriage outside of their ethnic group, and incidents of discrimination that they encountered. Demographic variables include language spoken in the home, religious preference, home ownership, ethnic origin of spouse, level of education, income, employment, age, and sex.